Visualization and segmentation of reciprocal cerebrocerebellar pathways in the healthy and injured brain. Issue 7 (14th April 2015) - Law, Nicole; Greenberg, Mark; Bouffet, Eric; Laughlin, Suzanne; Taylor, Michael D.; Malkin, David; Liu, Fang; Moxon‐Emre, Iska; Scantlebury, Nadia; Skocic, Jovanka; Mabbott, Donald
Abstract Detailed information regarding the neuroanatomy of reciprocal cerebrocerebellar pathways is based on well‐documented animal models. This knowledge has not yet been fully translated to humans, in that the structure of reciprocal cerebrocerebellar pathways connecting the cerebellum with frontal lobe has not been shown in its entirety. We investigated the impact of injury and age on cerebrocerebellar pathway microstructure using diffusion tensor imaging (DTI) and probabilistic tractography. We used medulloblastoma (MB) as an injury model due to the known impact of tumor/treatment on the cerebellum, one of the main nodes of cerebrocerebellar pathways. We delineated and segmented reciprocal cerebrocerebellar pathways connecting the cerebellum with frontal lobe in 38 healthy children (HC) and 34 children treated for MB, and compared pathway segment DTI measures between HC and MB and across three age cohorts: childhood, early adolescence, and late adolescence. Pathway compromise was evident for the MB group compared to HC, particularly within posterior segments (Ps<0.01). Though we found no age effect, group differences in microstructure were driven by pathway segment (posterior) and age cohort (adolescence), which may reflect the extent of injury to the posterior fossa following treatment for MB and age cohort differences in radiation treatment protocol in our sample. We have examined the microstructure of reciprocal cerebrocerebellar connections in the pediatric brain and have found that these pathways are injured in MB, a clinical population treated with surgery, radiation, and chemotherapy. Our findings support the late effects literature describing white matter injury emergence in the years following treatment for MB. Hum Brain Mapp 36:2615–2628, 2015. © 2015 Wiley Periodicals, Inc.